2015
DOI: 10.1007/s11356-015-4438-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a permeable reactive barrier to capture and degrade hydrocarbon contaminants

Abstract: A permeable reactive barrier (PRB) was installed during 2005/2006 to intercept, capture and degrade a fuel spill at the Main Power House, Casey Station, Antarctica. Here, evaluation of the performance of the PRB is conducted via interpretation of total petroleum hydrocarbon (TPH) concentrations, degradation indices and most probable number (MPN) counts of total heterotroph and fuel degrading microbial populations. Results indicate that locations which contained the lowest TPH concentrations also exhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…With ∼12 freeze–thaw cycles per year in the top 30 cm of Antarctic soil (S. Ferguson, Australian Antarctic Division, unpublished observations), ongoing release of total NH 3 and K + at 100 freeze–thaw cycles demonstrates the long‐term suitability of Zeopro™ to promote PHC degradation. However, it must be noted that while this experiment was conducted in deionised water, cations in groundwater and particle colonisation by microorganisms may alter the release rates of total NH 3 and K + from Zeopro™ .…”
Section: Discussionmentioning
confidence: 99%
“…With ∼12 freeze–thaw cycles per year in the top 30 cm of Antarctic soil (S. Ferguson, Australian Antarctic Division, unpublished observations), ongoing release of total NH 3 and K + at 100 freeze–thaw cycles demonstrates the long‐term suitability of Zeopro™ to promote PHC degradation. However, it must be noted that while this experiment was conducted in deionised water, cations in groundwater and particle colonisation by microorganisms may alter the release rates of total NH 3 and K + from Zeopro™ .…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that BC has a strong adsorption capacity to TC and CAP; with increasing influent concentration and flow rate, adsorption efficiency improves. Surface diffusion was the most common mass transfer mechanism for antibiotic adsorption [ 98 , 99 ].…”
Section: Review Of Previous Research On the Use Of Prbsmentioning
confidence: 99%
“…The effectiveness of petroleum hydrocarbon adsorption materials such as granular activated carbon (GAC) in PRBs has been well reported (Karanfil and Kilduff, 1999;Arora et al, 2011;Mumford et al, 2015). However, in the absence of biodegradation, the finite adsorption capacity of GAC presents issues associated with breakthrough, regeneration and disposal as a hazardous material.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled release nutrient (CRN) materials are therefore important for the sustained delivery of essential nutrients to particle-attached biofilms in PRBs (Freidman et al, submitted for publication). Mumford et al (2013Mumford et al ( , 2014Mumford et al ( , 2015 report the first application of soluble and nutrient-amended zeolite CRN materials to promote biodegradation in a sequenced PRB at Casey Station, Antarctica. Total petroleum hydrocarbon concentrations, degradation indices and microbial analyses support the application of CRN materials to promote biodegradation within PRBs .…”
Section: Introductionmentioning
confidence: 99%